(untitled) (Orfeu, 2025)
The article presents the problem for understanding the category of labor in the musical field, as represented by dualist ontological conceptions that oppose idea and matter. It argues that such conceptions were responsible for establishing a division between the status of artist and music worker, resulting –under the prevalence of fetishized social relations –in the concealment of the musician’s labor. As a way to overcome this impasse, it proposes the Marxist-Engelsian discovery of labor as a foundational category of social being, including Lukács’ contribution: through labor, the social being produces a new objectivity. Through the mediation of consciousness, natural matter is organized by labor, giving rise to ontologically new entities and relationships, syntheses between idea and the natural world: objectified ideas. In this way, the inherited contradiction between art and labor is overcome, opening up the possibility of revealing the real and of the praxis of constructing human generality-for-itself.